Sosialisasi Manajemen Bumdes di Desa Uwedikan Kecamatan Luwuk Timur - Siswadi Sululing; Yanti Mutalib (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service is entitled: "Socialization of Management of Village Owned Enterprises (BUMDes)" which was carried out in Uwedikan Village, East Luwuk District, Banggai Regency, Central Sulawesi Province. The purpose of this service is to increase knowledge about bumdes management for the uwedikan bumdes management in particular and the uwedikan community in general. This activity is a socialization involving students participating in real work lectures at the University of Muhammadiyah Luwuk Posko Luwuk City. The method of implementing this service activity uses counseling about the socialization of bumdes management which consists of 4 (four) stages, namely: 1). Socialization stage, 2). preparation stage and 3). Implementation stage and 4). Evaluation stage. The result of the implementation of community service activities regarding the socialization of bumdes management is the transfer of knowledge to the bumdes management so that it becomes the basis for managing bumdes to be better, develop and advance in the future so that it can become one of the sources of village finance, namely village original income. The conclusion is the result of the implementation of community service activities regarding the socialization of bumdes management to increase knowledge as a provision in managing the bumdes to be better, while the suggestion is that this socialization can be continued by the community by strengthening the bumdes institution, so as to increase new economic resources for the Uwedikan village community. and the results of this socialization are very useful so that it can be applied by the bumdes management in the Uwedikan village.